Radiation-resistant and electromagnetic-shielding resin-based composite sheet as well as preparation method and application thereof
By depositing nano-scale Fe3O4 on glass fibers and improving the dispersion of ultrafine barium sulfate, the problem of insufficient radiation resistance and electromagnetic shielding capabilities of PEEK resin-based composites is solved, and efficient gamma radiation shielding and electromagnetic shielding performance is achieved. It is suitable for In stealth technology such as nuclear-powered aircraft carriers.
Patent Information
- Application Number
- CN202411620236.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-11-14
AI Technical Summary
The radiation resistance and electromagnetic shielding capabilities of PEEK resin-based composites are weak, and the uneven dispersion of powder materials in the existing methods leads to limited performance improvement.
Nano-scale Fe3O4 was deposited on glass fibers by chemical liquid phase co-deposition, and the dispersion of ultrafine barium sulfate in the resin matrix was improved by using slurry impregnation method and hot pressing method to prepare composite sheets.
It significantly improves the gamma radiation absorption dose and electromagnetic shielding efficiency of PEEK materials, with a maximum shielding efficiency of 67dB, realizing the application in stealth technologies such as nuclear-powered aircraft carriers and nuclear power plants.
Smart Images

Figure CN119119539A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of resin-based composite materials, and in particular relates to a radiation-resistant and electromagnetic-shielding resin-based composite sheet material and a preparation method and application thereof. Background Art
[0002] Polyetheretherketone (PEEK) has become a promising thermoplastic resin matrix for composite materials due to its excellent physical properties such as mechanical strength and chemical stability such as acid and alkali resistance and hydrolysis resistance. Due to its stable chemical structure, PEEK also has a certain radiation resistance, but its radiation resistance is poor. Glass fiber has inorganic metal oxide components and a relatively tight structure. The interweaving arrangement between the fibers forms a certain barrier, which has a certain absorption and blocking effect on radiation within a certain energy range. Therefore, glass fiber reinforced polyetheretherketone composite materials have been widely used in the field of radiation resistance. However, the radiation resistance and electromagnetic shielding capabilities of PEEK resin-based composite materials are still weak. Under special circumstances, their radiation resistance and electromagnetic shielding performance still do not meet the requirements. In order to further improve the radiation resistance and electromagnetic shielding capabilities of PEEK resin-based composite materials, one or more of the powder materials with radiation resistance and electromagnetic shielding capabilities such as silicon oxide, bismuth oxide, and ferrite are usually introduced in the form of blending. Then, the powder with radiation resistance and electromagnetic shielding ability in the composite material obtained by the above method has the problems of uneven dispersion and discontinuity, so that the radiation resistance and electromagnetic shielding ability of the composite material still need to be improved. The present invention deposits nano-scale Fe3O4 on glass fiber by chemical liquid phase co-deposition method, improves the poor dispersion of ultrafine barium sulfate in the resin matrix by hydrolysis reaction of silane coupling agent, and prepares a PEEK resin-based composite sheet with radiation protection and electromagnetic shielding performance by mud impregnation method and hot pressing molding method. The application of PEEK material in stealth technology such as nuclear-powered aircraft carriers, nuclear-powered submarines, nuclear power plant units and drones is realized. Summary of the invention
[0003] The purpose of the present invention is to improve the radiation resistance and electromagnetic shielding capabilities of a polyetheretherketone resin matrix, and to provide a radiation-resistant and electromagnetic-shielding resin-based composite sheet, a preparation method and an application thereof.
[0004] The technical solution of the present invention is as follows: One of the purposes of the present invention is to provide a method for preparing a radiation-resistant and electromagnetic shielding resin-based composite sheet, the method being carried out according to the following steps: S1: placing the glass fiber in a mixed acid solution for surface pretreatment, then ultrasonically immersing it in an aqueous solution of a silane coupling agent, washing and drying it to obtain a modified glass fiber; S2: placing the modified glass fiber in a bovine serum albumin aqueous solution containing Fe3O4 for electrophoretic deposition, washing with anhydrous ethanol and drying to obtain Fe3O4 modified glass fiber; S3: Put 50-90 parts of polyetheretherketone powder, 5-10 parts of ultrafine barium sulfate, 1-3 parts of silane coupling agent and 1-3 parts of auxiliary filler into a mixer, mix well, add water and stir to obtain mud; S4: The slurry and Fe3O4 modified glass fiber are impregnated and extruded to obtain a PEEK composite glass fiber prepreg tape, and finally a composite sheet is obtained by hot pressing.
[0005] It is further defined that the surface pretreatment in S1 is: ultrasonic treatment at 40-70° C. for 1-3 h in a mixed acid solution, wherein the mixed acid solution consists of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1-2:1.
[0006] It is further defined that the volume concentration of the aqueous solution of the silane coupling agent in S1 is 5-15%, and the ultrasonic immersion is 10-30 minutes.
[0007] It is further defined that the average diameter of the glass fibers in S1 is 7-10 μm.
[0008] Further defined, soaking in S1 for 10 to 30 minutes.
[0009] It is further defined that the concentration of bovine serum albumin in the bovine serum albumin aqueous solution containing Fe3O4 in S2 is 0.03~0.05g / mL, the concentration of Fe3O4 is 0.1~0.25g / mL, and the electrophoretic deposition is 10~30min.
[0010] It is further defined that Fe3O4 in S2 contains -COOH and has a mesh size of 800~3000 mesh.
[0011] It is further defined that the mesh size of the polyetheretherketone powder in S3 is 800-1000 mesh and the density is 1.3 g / cm 3 , the melt index is 5~120 g / 10min, and the mesh number of ultrafine barium sulfate is 800~3000 mesh.
[0012] It is further defined that the volume concentration of the mud obtained by S3 is 10-30%.
[0013] It is further defined that the auxiliary filler in S3 includes at least one of an esterification reaction catalyst and a lubricant.
[0014] It is further defined that the esterification reaction catalyst is composed of 4-dimethylaminopyridine and dicyclohexylcarbodiimide, and the lubricant includes at least one of pentaerythritol stearate, calcium stearate, magnesium stearate, barium stearate, and N,N'-ethylenebisstearamide.
[0015] It is further defined that the mass ratio of polyetheretherketone to Fe3O4 modified glass fiber in the slurry in S4 is 50~90:5~40.
[0016] The second object of the present invention is to provide a radiation-resistant and electromagnetic-shielding resin-based composite sheet prepared by the above method.
[0017] The third object of the present invention is to provide a radiation-resistant and electromagnetic-shielding resin-based composite sheet prepared by the above method for use in the field of radiation resistance and electromagnetic shielding.
[0018] Compared with the prior art, the present invention has the following advantages: The present invention deposits nano-scale ferrosoferric oxide on glass fiber by a chemical liquid phase co-deposition method, and at the same time, adds ultrafine barium sulfate and adopts a mud impregnation method to synergistically improve the electromagnetic shielding performance and anti-γ-ray radiation performance of the PEEK material, with a maximum shielding effectiveness of 67dB, and a γ-ray radiation dose increased by 1.76 times compared with that of a pure PEEK resin matrix, with excellent comprehensive performance, thus realizing the application of PEEK materials in stealth technologies such as nuclear-powered aircraft carriers, nuclear-powered submarines, nuclear power plant units, and drones. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a top view of the composite sheet obtained in Example 1 of the present invention after being colored; Figure 2 The composite sheet obtained in Example 1 of the present invention is colored relative to Figure 1 Actual photos from different angles. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0021] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0022] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.
[0023] Fe3O4 (containing -COOH) (McLean reagent, 1317-61-9) and ultrafine barium sulfate (manufacturer: NACALAI TESQUE, INC., brand: 03834-55) were used in the following examples.
[0024] Example 1 The method for preparing the radiation-resistant and electromagnetic-shielding resin-based composite sheet of this embodiment is carried out according to the following steps: S1: 25 parts of glass fibers were placed in a mixed solution of concentrated nitric acid and concentrated sulfuric acid (volume ratio of 2:1), ultrasonically treated at 60°C for 2 hours for surface pretreatment, washed with anhydrous ethanol and dried, and then ultrasonically immersed in an aqueous solution of 10% by volume of silane coupling agent A-174 for 20 minutes, washed with anhydrous ethanol and dried to obtain modified glass fibers; S2: placing the modified glass fiber in a bovine serum albumin aqueous solution containing Fe3O4 (Fe3O4 contains -COOH, and the mesh size is 800-3000 mesh), wherein the bovine serum albumin concentration in the bovine serum albumin aqueous solution containing Fe3O4 is 0.05 g / mL, and the concentration of Fe3O4 is 0.2 g / mL, electrophoretically depositing the Fe3O4 for 20 minutes using a chemical liquid phase coprecipitation method, washing with anhydrous ethanol and drying, to obtain Fe3O4 modified glass fiber; S3: 70 parts of polyetheretherketone powder (mesh size 800-1000 mesh, density 1.3 g / cm 3 , melt index is 12g / 10min), 5 parts of superfine barium sulfate (mesh size is 800-3000 mesh), 3 parts of silane coupling agent A-174, 1 part of esterification reaction catalyst (4-dimethylaminopyridine and dicyclohexylcarbodiimide have a molar ratio of 1:1) and 1 part of pentaerythritol stearate are put into a mixer and mixed for 20 minutes, and then water is added and stirred to obtain a raw material slurry with a volume fraction of 20%; S4: The raw material slurry and Fe3O4 modified glass fiber were impregnated and extruded to obtain PEEK composite glass fiber prepreg tape; finally, 6 layers of the prepared PEEK composite glass fiber prepreg tape were placed alternately vertically and horizontally, and hot pressed at 380°C and 6 MPa to obtain a composite sheet, which was recorded as GFPEEK-25.
[0025] Example 2 The method for preparing the radiation-resistant and electromagnetic-shielding resin-based composite sheet of this embodiment is carried out according to the following steps: S1: 10 parts of glass fibers were placed in a mixed solution of concentrated nitric acid and concentrated sulfuric acid (volume ratio of 2:1), ultrasonically treated at 60°C for 2 hours for surface pretreatment, washed with anhydrous ethanol and dried, and then ultrasonically soaked in an aqueous solution of 10% by volume of silane coupling agent A-174 for 20 minutes, washed with anhydrous ethanol and dried to obtain modified glass fibers; S2: placing the modified glass fiber in a bovine serum albumin aqueous solution containing Fe3O4 (Fe3O4 contains -COOH, and the mesh size is 800-3000 mesh), wherein the bovine serum albumin concentration in the bovine serum albumin aqueous solution containing Fe3O4 is 0.05 g / mL, and the concentration of Fe3O4 is 0.2 g / mL, electrophoretically depositing the Fe3O4 for 20 minutes using a chemical liquid phase coprecipitation method, washing with anhydrous ethanol and drying, to obtain Fe3O4 modified glass fiber; S3: 85 parts of polyetheretherketone powder (mesh size 800-1000 mesh, density 1.3 g / cm 3 , melt index is 12g / 10min), 5 parts of superfine barium sulfate (mesh size is 800-3000 mesh), 3 parts of silane coupling agent A-174, 1 part of esterification reaction catalyst (4-dimethylaminopyridine and dicyclohexylcarbodiimide have a molar ratio of 1:1) and 1 part of pentaerythritol stearate are put into a mixer and mixed for 20min, then water is added and stirred to obtain a mud with a volume fraction of 20%; S4: The raw material slurry and Fe3O4 modified glass fiber were impregnated and extruded to obtain PEEK composite glass fiber prepreg tape; finally, 6 layers of the prepared PEEK composite glass fiber prepreg tape were placed alternately vertically and horizontally, and hot pressed at 380°C and 6 MPa to obtain a composite sheet, which was recorded as GFPEEK-10.
[0026] Example 3 The method for preparing the radiation-resistant and electromagnetic-shielding resin-based composite sheet of this embodiment is carried out according to the following steps: S1: 15 parts of glass fiber were placed in a mixed solution of concentrated nitric acid and concentrated sulfuric acid (volume ratio of 2:1), ultrasonically treated at 60°C for 2 hours for surface pretreatment, washed with anhydrous ethanol and dried, then immersed in an aqueous solution of 10% by volume of silane coupling agent A-174 for 20 minutes, washed with anhydrous ethanol and dried to obtain modified glass fiber; S2: placing the modified glass fiber in a bovine serum albumin aqueous solution containing Fe3O4 (Fe3O4 contains -COOH, and the mesh size is 800-3000 mesh), wherein the bovine serum albumin concentration in the bovine serum albumin aqueous solution containing Fe3O4 is 0.05 g / mL, and the concentration of Fe3O4 is 0.2 g / mL, electrophoretically depositing the Fe3O4 for 20 minutes using a chemical liquid phase coprecipitation method, washing with anhydrous ethanol and drying, to obtain Fe3O4 modified glass fiber; S3: 80 parts of polyetheretherketone powder (mesh size 800-1000 mesh, density 1.3 g / cm 3, melt index is 5-120 g / 10min), 5 parts of superfine barium sulfate (mesh size is 800-3000 mesh), 3 parts of silane coupling agent A-174, 1 part of esterification reaction catalyst (4-dimethylaminopyridine and dicyclohexylcarbodiimide have a molar ratio of 1:1) and 1 part of pentaerythritol stearate are put into a mixer and mixed for 20 minutes, and then water is added and stirred to obtain a mud with a volume fraction of 20%; S4: The raw material slurry and Fe3O4 modified glass fiber were impregnated and extruded to obtain PEEK composite glass fiber prepreg tape; finally, 6 layers of the prepared PEEK composite glass fiber prepreg tape were placed alternately vertically and horizontally, and hot pressed at 380°C and 6 MPa to obtain a composite sheet, which was recorded as GFPEEK-15.
[0027] Example 4 The method for preparing the radiation-resistant and electromagnetic-shielding resin-based composite sheet of this embodiment is carried out according to the following steps: S1: 40 parts of glass fibers were placed in a mixed solution of concentrated nitric acid and concentrated sulfuric acid (volume ratio of 2:1), ultrasonically treated at 60°C for 2 hours for surface pretreatment, washed with anhydrous ethanol and dried, and then immersed in an aqueous solution of 10% by volume of silane coupling agent A-174 for 20 minutes, washed with anhydrous ethanol and dried to obtain modified glass fibers; S2: placing the modified glass fiber in a bovine serum albumin aqueous solution containing Fe3O4 (Fe3O4 contains -COOH, and the mesh size is 800-3000 mesh), wherein the bovine serum albumin concentration in the bovine serum albumin aqueous solution containing Fe3O4 is 0.05 g / mL, and the concentration of Fe3O4 is 0.2 g / mL, electrophoretically depositing the Fe3O4 for 20 minutes using a chemical liquid phase coprecipitation method, washing with anhydrous ethanol and drying, to obtain Fe3O4 modified glass fiber; S3: 50 parts of polyetheretherketone powder (mesh size 800-1000 mesh, density 1.3 g / cm 3 , melt index is 5-120 g / 10min), 10 parts of superfine barium sulfate (mesh size is 800-3000 mesh), 3 parts of silane coupling agent A-174, 1 part of esterification reaction catalyst (4-dimethylaminopyridine and dicyclohexylcarbodiimide have a molar ratio of 1:1) and 1 part of pentaerythritol stearate are put into a mixer and mixed for 20 minutes, and then water is added and stirred to obtain a mud with a volume fraction of 20%; S4: The raw material slurry and Fe3O4 modified glass fiber are impregnated and extruded to obtain PEEK composite glass fiber prepreg tape; finally, 6 layers of the prepared PEEK composite glass fiber prepreg tape are placed alternately vertically and horizontally, and hot pressed at 380°C and 6 MPa to obtain a composite sheet, which is denoted as GFPEEK-40.
[0028] Comparative Example 1 S1: 25 parts of glass fibers were placed in a mixed solution of concentrated nitric acid and concentrated sulfuric acid (volume ratio of 2:1), ultrasonically treated at 60°C for 2 hours for surface pretreatment, washed with anhydrous ethanol and dried, and then ultrasonically immersed in an aqueous solution of 10% by volume of silane coupling agent A-174 for 20 minutes, washed with anhydrous ethanol and dried to obtain modified glass fibers; S2: 75 parts of polyetheretherketone powder (mesh size 800-1000 mesh, density 1.3 g / cm 3 , melt index is 12g / 10min), 3 parts of silane coupling agent A-174, 1 part of esterification reaction catalyst (4-dimethylaminopyridine and dicyclohexylcarbodiimide have a molar ratio of 1:1) and 1 part of pentaerythritol stearate are put into a mixer and mixed for 20min, then water is added and stirred to obtain a raw material slurry with a volume fraction of 20%; S3: The raw material slurry is impregnated and extruded with glass fiber to obtain a PEEK composite glass fiber prepreg tape; finally, the prepared PEEK composite glass fiber prepreg tape is placed in 6 layers alternately vertically and horizontally, and hot pressed at 380°C and 6 MPa to obtain a composite sheet, which is denoted as GFPEEK-1.
[0029] Comparative Example 2 S1: 25 parts of glass fibers were placed in a mixed solution of concentrated nitric acid and concentrated sulfuric acid (volume ratio of 2:1), ultrasonically treated at 60°C for 2 hours for surface pretreatment, washed with anhydrous ethanol and dried, and then ultrasonically immersed in an aqueous solution of 10% by volume of silane coupling agent A-174 for 20 minutes, washed with anhydrous ethanol and dried to obtain modified glass fibers; S2: 75 parts of polyetheretherketone powder (mesh size 800-1000 mesh, density 1.3 g / cm 3 , melt index is 12g / 10min), 5 parts of superfine barium sulfate (mesh size is 800-3000 mesh), 3 parts of silane coupling agent A-174, 1 part of esterification reaction catalyst (4-dimethylaminopyridine and dicyclohexylcarbodiimide have a molar ratio of 1:1) and 1 part of pentaerythritol stearate are put into a mixer and mixed for 20 minutes, and then water is added and stirred to obtain a raw material slurry with a volume fraction of 20%; S3: The raw material slurry and the modified glass fiber are impregnated and extruded to obtain a PEEK composite glass fiber prepreg tape; finally, 6 layers of the prepared PEEK composite glass fiber prepreg tape are placed alternately vertically and horizontally, and hot pressed at 380°C and 6 MPa to obtain a composite sheet, which is denoted as GFPEEK-2.
[0030] Comparative Example 3 S1: 25 parts of glass fibers were placed in a mixed solution of concentrated nitric acid and concentrated sulfuric acid (volume ratio of 2:1), ultrasonically treated at 60°C for 2 hours for surface pretreatment, washed with anhydrous ethanol and dried, and then ultrasonically immersed in an aqueous solution of 10% by volume of silane coupling agent A-174 for 20 minutes, washed with anhydrous ethanol and dried to obtain modified glass fibers; S2: placing the modified glass fiber in a bovine serum albumin aqueous solution containing Fe3O4 (Fe3O4 contains -COOH, and the mesh size is 800-3000 mesh), wherein the bovine serum albumin concentration in the bovine serum albumin aqueous solution containing Fe3O4 is 0.05 g / mL, and the concentration of Fe3O4 is 0.2 g / mL, electrophoretically depositing the Fe3O4 for 20 minutes using a chemical liquid phase coprecipitation method, washing with anhydrous ethanol and drying, to obtain Fe3O4 modified glass fiber; S3: 75 parts of polyetheretherketone powder (mesh size 800-1000 mesh, density 1.3 g / cm 3 , melt index is 12g / 10min), 3 parts of silane coupling agent A-174, 1 part of esterification reaction catalyst (4-dimethylaminopyridine and dicyclohexylcarbodiimide have a molar ratio of 1:1) and 1 part of pentaerythritol stearate are put into a mixer and mixed for 20min, then water is added and stirred to obtain a raw material slurry with a volume fraction of 20%; S4: The raw material slurry and Fe3O4 modified glass fiber were impregnated and extruded to obtain PEEK composite glass fiber prepreg tape; finally, 6 layers of the prepared PEEK composite glass fiber prepreg tape were placed alternately vertically and horizontally, and hot pressed at 380°C and 6 MPa to obtain a composite sheet, which was recorded as GFPEEK-3.
[0031] Detection test (I): Using cesium-137 as the γ-ray source, a semiconductor detector was used to test the irradiation dose of γ-rays absorbed by a composite sheet with a size of 40×40×5mm and a mass of 15g. The photoelectric peak at 0.66MeV was taken, and the linear absorption coefficient was fitted using the least squares principle to calculate the radiation absorption dose of γ-rays. The results are shown in Table 1.
[0032] Detection test (II): The shielding effectiveness of the sample with a size of 40×40×5mm was measured using a small window method shielding effectiveness test box. The test box frequency range is 1GHz~18GHz, shielding effectiveness≥90dB (to ensure the accuracy of the test) The sample fixing method is card-mounted. The signal interface type supports N-type and SMA(F) interfaces. The test results are shown in Table 2.
[0033] The γ absorption coefficients of Examples 1-4 and Comparative Examples 1-3 are shown in Table 1, and the shielding energy efficiencies of Examples 1-4 and Comparative Examples 1-3 are shown in Table 2.
[0034] Table 1
[0035] Table 2
[0036] As can be seen from Table 1-2, the maximum shielding effectiveness of the composite sheet of the present invention is 67dB (Example 4). Among them, the 25% glass fiber composite PEEK material (Example 1) shows the maximum γ irradiation and shielding effectiveness after adding nano-Fe3O4 (containing -COOH) and ultrafine barium sulfate. Compared with the common GF / PEEK material (Comparative Example 1), the γ radiation absorption dose increased from 1062Mrad to 2931Mrad, an increase of about 1.76 times.
[0037] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a radiation-resistant and electromagnetic-shielding resin-based composite sheet, characterized in that: The method: S1: placing the glass fiber in a mixed acid solution for surface pretreatment, then ultrasonically immersing it in an aqueous solution of a silane coupling agent, washing and drying it to obtain a modified glass fiber; S2: placing the modified glass fiber in a bovine serum albumin aqueous solution containing Fe3O4 for electrophoretic deposition, washing with anhydrous ethanol and drying to obtain Fe3O4 modified glass fiber; S3: Put 50-90 parts of polyetheretherketone powder, 5-10 parts of ultrafine barium sulfate, 1-3 parts of silane coupling agent and 1-3 parts of auxiliary filler into a mixer, mix well, add water and stir to obtain mud; S4: The slurry and Fe3O4 modified glass fiber are impregnated and extruded to obtain a polyetheretherketone composite glass fiber prepreg tape, and finally a composite sheet is obtained by hot pressing.
2. The method according to claim 1, characterized in that Surface pretreatment in S1: ultrasonic treatment at 40-70°C for 1-3h in a mixed acid solution, wherein the mixed acid solution is composed of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1-2:
1.
3. The method according to claim 1, characterized in that The volume concentration of the aqueous solution of the silane coupling agent in S1 is 5-15%, and the ultrasonic immersion is 10-30 minutes.
4. The method according to claim 1, characterized in that: The concentration of bovine serum albumin in the bovine serum albumin aqueous solution containing Fe3O4 in S2 is 0.03~0.05g / mL, the concentration of Fe3O4 is 0.1~0.25g / mL, and the electrophoretic deposition is 10~30min.
5. The method according to claim 1, characterized in that The auxiliary filler in S3 includes at least one of an esterification reaction catalyst and a lubricant.
6. The method according to claim 5, characterized in that The esterification reaction catalyst is composed of 4-dimethylaminopyridine and dicyclohexylcarbodiimide, and the lubricant comprises at least one of pentaerythritol stearate, calcium stearate, magnesium stearate, barium stearate and N,N'-ethylenebisstearic acid amide.
7. The method according to claim 1, characterized in that The volume concentration of the mud obtained in S3 is 10~30%.
8. The method according to claim 1, characterized in that The mass ratio of polyetheretherketone to Fe3O4 modified glass fiber in the slurry described in S4 is 50~90:5~40.
9. A radiation-resistant and electromagnetic-shielding resin-based composite sheet prepared according to the method according to any one of claims 1 to 8.
10. Use of the resin-based composite sheet material as claimed in claim 9 in the fields of radiation resistance and electromagnetic shielding.
Citation Information
Patent Citations
Polyetheretherketone-base composite electromagnetic shielding material and preparation method thereof
CN102321338A
Nano-scale Fe3O4-modified graphene-coated glass fiber composite material and preparation method thereof
CN107354500A
Methods for preparing magnetic powder material and magnet, process for prepartion of resin composition and process for producing a powder molded product
US5256326A
Cited By
Composite forming method and electrothermal infrared application of flaky polyether-ether-ketone-montmorillonite fiber fabric
CN120152078A
